(untitled) (Journal of Oriental Studies, 2018)
In this article we comprehensively conducted the differences between two-part sentences in Chinese and Kazakh languages. Chinese is SVO form - language, in chinese the verb is formed by peculiarities of forming verbal sentences. The are not any big morphological changes. In any case: «peculiarity remains + verb is the basis + result remains». In sentences the subject, the object and adverbial modifier are placed before the predicate. The word - combination and word formation are formed by this way. As long as the auxiliary word and prepositions form the member of the sentence. Therefore, the words tend to change places, members of the sentence are widely used. However, in both languages the role of the subject and predicate remains unchanged.